The Role of Mismatch Repair in Glioblastoma Multiforme Treatment Response and Resistance - Leelatian, Nalin; Hong, Christopher S; Bindra, Ranjit S (Neurosurgery clinics of North America, 2021)
Mismatch repair (MMR) is a highly conserved DNA repair pathway that is critical for the maintenance of genomic integrity. This pathway targets base substitution and insertion-deletion mismatches, which primarily arise from replication errors that escape DNA polymerase proof-reading function. Here, the authors review key concepts in the molecular mechanisms of MMR in response to alkylation damage, approaches to detect MMR status in the clinic, and the clinical relevance of this pathway in glioblastoma multiforme treatment response and resistance.